PENGARUH UKURAN DEWAN KOMISARIS DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAN - TJOKRO B11110005, ERIKA YUDHA (Jurnal Manajemen Update, 2014)
Corporate social responsibility disclosure has been one of the most discussed topics by many people around the world. This topic is deemed to be important because it is related to the society and nature viability. The purpose of this study is to investigate the influence of the board of commissioners’ size and the board of independent commissioners’ proportion to the corporate social responsibility disclosure along with the firm’s size as the control variable. This is a quantitative study by using panel data that focuses on mining companies listed on Indonesia Stock Exchange. There are 26 companies in 2011-2012 that are being used as samples by applying purposive sampling technique. This study uses content analysis as method to determine the extent of corporate social responsibility. Based on regression analysis, the results show that there is a statistically significant relationship between board of commissioners’ size with corporate social responsibility disclosure.  On the contrary, there is no statistically significant relationship between board of independent commissioners’ proportion to corporate social responsibility disclosure. Keywords  : Board of commissioners’ size, Board of independent commissioners’ proportion, Corporate social responsibility disclosure